Enhanced mechanical and interfacial performances of carbon fiber reinforced composites with low percentage of amine functionalized graphene - Choudhury D.N.; Pareta A.S.; Rajesh A.K.; Panda S.K. (My University, 2025)
This paper reports improvement in the tensile, flexural and interlaminar shear strength (ILSS) properties of ADG-NH2/Epoxy/CFRP composites at low filler content. Five symmetrical CFRP composite laminates were prepared through wet layup process assisted by vacuum bagging technique with varying wt% proportions (0.25, 0.5, 0.75 and 1) of ADG-NH2/Epoxy. Tensile tests, short beam shear test and flexural tests were carried out as per ASTM D3039, ASTM D2344 and ASTM 790-10 respectively to assess the effect of the ADG-NH2 functionalized nano additives on their mechanical properties. The variation in ILSS were studied for varying temperatures (room temperature, 35, 50, 75, 85, & 100°C for each type of ADG-NH2/Epoxy wt% (neat, 0.25, 0.5, 0.75 & 1)) of ADG-NH2/Epoxy/CFRP composites. The ILSS was enhanced up to ∼27% for 0.5 wt% of ADG-NH2 reinforced CFRP at room temperature but reduced with the higher concentrations (0.75 wt% & 1 wt%). It was observed that ILSS reduced with gradual temperature variations up to 100°C w.r.t room temperature. But an increment was observed up to 0.5 wt% for ADG-NH2 for all temperature. Form the test results, it has been recorded an improvement in mechanical properties that is, the elastic modulus by ∼18%, ultimate tensile strength by ∼21%, % elongation at break by∼19% and toughness by∼28% for the 0.5 wt% of ADG-NH2 graphene nano additive reinforced CFRP composite laminates as compared to neat epoxy CFRP laminates. Results also show the augmentation in the Max load by ∼24%, flexural strength by ∼33%, flexural modulus by ∼43%, and flexural strain by ∼26% were observed for the 0.5 wt% of ADG-NH2 graphene nano additive reinforced CFRP composite laminates as compared to neat epoxy CFRP composite laminates. Fractographic studies of fractured surface using SEM analyses shows better adhesion mechanisms which supports the augmentation in mechanical properties with addition of amine functionalized graphene to CFRP laminate. Highlights: Reinforcement of amine functionalized (ADG-NH2) graphene in the epoxy matrix and incorporation with carbon fibers to enhance the interfacial and flexural properties. Evaluation of temperature effects on interlaminar shear strength properties of amine functionalized CFRP composites Improvements in tensile, ILSS and flexural properties observed for a low percentage (0.5 wt%) of ADG-NH2 graphene reinforced CFRP composite laminates. Use of aerospace grade epoxy and resin with amine functionalized graphene for further use in aerospace industry applications. © 2024 Society of Plastics Engineers.